Refining Vegetable Oils: Chemical and Physical Refining. (11th January 2022) - Gharby, Said
Abstract : This review presents recent technologies involved in vegetable oil refining as well as quality attributes of crude oils obtained by mechanical and solvent extraction. Usually, apart from virgin oils, crude oils cannot be consumed directly or incorporated into various food applications without technological treatments (refining). Indeed, crude oils like soybean, rapeseed, palm, corn, and sunflower oils must be purified or refined before consumption. The objective of such treatments (chemical and physical refining) is to get a better quality, a more acceptable aspect (limpidity), a lighter odor and color, longer stability, and good safety through the elimination of pollutants while minimizing oil loss during processing. However, the problem is that refining removes some essential nutrients and often generates other undesirable compounds such as 3-MCPD-esters and trans-fatty acids. These compounds directly influence the safety level of refined oil. Advantages and drawbacks of both chemical and physical refining were discussed in the light of recent literature. Physical refining has several advantages over chemical one.